(untitled) (Scholars’ Journal, 2022)
This study, “Causes of low performance in English at college level: Teachers’ Perspectives,” aimed to explore the teachers’ perspectives on the causes of low performance in English and suggestions forth improvement for the college level students. The data were collected from twenty teachers teaching at the college level in the Far Western part of Nepal using a general qualitative research design. The study used a questionnaire containing open ended questions to collect their perspectives and shared the question using Google form. Collected data were analyzed, forming two themes based on the questions: causes of low performance and suggestions for improvement. The collected data showed that classroom interaction, teaching methods, learners, curriculum, and evaluation system are the main causes of low performance. They have suggested increasing interaction in the classroom, changing teaching method sat the college level, revising the existing courses, and changing the examination system in the university to improve the level of performance of the students, especially at the college level.